The demand for money in Malaysia (1982-1999) - Sia, Sheau Ai (Universiti Malaysia Sarawak (UNIMAS), 2003)
This research is use to estimate the function of money demand, M2 in Malaysia from 1982 to 1999. This research has examined empirically the factors that influence demand of money in Malaysia